Does Happiness Converge? - Apergis, Nicholas; Georgellis, Yannis (Springer Netherlands, 2013)
Using the Phillips and Sul (Econometrica 75:1771–1855, 2007) club convergence and clustering procedure, we examine happiness convergence dynamics across Europe. Although we reject the hypothesis of full convergence, we find evidence of distinct happiness convergence clubs. Against the background of a weak link between income and happiness in the existing literature, we advocate that happiness convergence is a legitimate policy goal on its own right as well as a useful barometer of changes in the political landscape, societal values, and citizens’ sentiments about developments in the European Union.